Coupling of Agriculture with the Tourism for the Sustainable Livelihood Development of Small – Scale Farmers (Special Reference to Southern Province) - Jayamali, L.U.C.C.; Shammika, D.L.A.H. (University of Jaffna, 2021)
Agrotourism is which is also known as a type of rural tourism. Many parts of Sri Lanka are still didn’t attained that much of urbanism therefore, those areas acting as preserving grounds for the rural agricultural characteristics. Couple agriculture with the tourism as an Agri - entrepreneurial sector, an alternative tourism sector which could be a strategical method to involve more women and youth in to agricultural area in the Southern province in order to improve their livelihood in a sustainable manner. This study carried out based on the grounded theory method since the research work was a social study which have been done thorough focused interviews with the 50 small-scale farmers and fishermen and 20 surrounding community people in Dikkubura weekend farm and paddy cultivation, Stilt fishing at Koggala and Home Gardening and fishing village at Kahandamodara. A questioner was performed by 20 local and foreign visitors to Sri Lanka. The feeding grounds of the research were selected for reason of practicing ecological agriculture. As the parameters View on community based agrotourism by farmers and fishermen, View on economic, social and environmental impacts of community based agrotourism by the community, Knowledge about the agrotourism, expectations from the agrotourism by tourists were measured. Participants were had positive perceptions regarding the impact of agrotourism on economy than its negative with higher difference where social and environmental impacts also showed positive but with minor difference than the negative. The interviews were coded and a theory was derived and it was concluded that there is a generation of conflict between government and community regarding agro tourism establishment though it had huge potentials.
Keywords: agrotourism; ecological agriculture; small scale farming